2008
DOI: 10.1152/jn.01131.2007
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Network States by Striatal Cell Assemblies

Abstract: Correlated activity in cortico-basal ganglia circuits plays a key role in the encoding of movement, associative learning and procedural memory. How correlated activity is assembled by striatal microcircuits is not understood. Calcium imaging of striatal neuronal populations, with single-cell resolution, reveals sporadic and asynchronous activity under control conditions. However, N-methyl-d-aspartate (NMDA) application induces bistability and correlated activity in striatal neurons. Widespread neurons within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
405
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(445 citation statements)
references
References 57 publications
22
405
0
Order By: Relevance
“…We apply our multiple spiketrain analysis to the outputs of this model to find groups of synchronised neurons at multiple time-scales. We then show that, with realistic in vivo background input, small assemblies of synchronised MSNs spontaneously appear, consistent with experimental observations (Carrillo-Reid et al, 2008), and that the number of assemblies and the time-scale of synchronisation is strongly dependent on the simulated concentration of dopamine.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…We apply our multiple spiketrain analysis to the outputs of this model to find groups of synchronised neurons at multiple time-scales. We then show that, with realistic in vivo background input, small assemblies of synchronised MSNs spontaneously appear, consistent with experimental observations (Carrillo-Reid et al, 2008), and that the number of assemblies and the time-scale of synchronisation is strongly dependent on the simulated concentration of dopamine.…”
Section: Introductionsupporting
confidence: 83%
“…For our present purposes, we wanted to find groups of co-active or mutually antagonistic MSNs that could form the basis for competitive dynamics within the striatum. In addition, we studied this input regime to see if the reported striatal cell clusters spontaneously formed in vitro (Carrillo-Reid et al, 2008) could be identified in our model. However, analysis methods suitable for exploratory analysis of such large spike-train data-sets are lacking (Brown et al, 2004).…”
Section: Detecting Groups Of Synchronised Cells In Multi-unit Datamentioning
confidence: 99%
See 3 more Smart Citations